How do health shocks affect preventive behaviours? An empirical examination of the mediating role of perceived risk from a longitudinal study in China - Yi Yang; Peng Zhang; Xichen Wang (BMJ Open, 2025)
Objectives Against the heavy burden of non-communicable diseases and the lack of preventive behaviours (PB) in China, health shocks (HSs), as a trigger, provide the teachable moment for promoting PB with a role of perceived risk (PR) in this process being discussed. The aim of this study is to examine four hypotheses on the impact of HS on PB and whether PR is mediating the relationship.Design A retrospective cohort.Setting Panel data of the China Health and Retirement Longitudinal Study, a well-designed nationally representative survey of Chinese over 45 years old in 2015 and 2018 waves.Participants A total of 9888 respondents were included, who were over 45 years old, followed up in both waves, and had no chronic diseases in 2015, after propensity score matching.Primary outcome measures The change of PB including smoking status, alcohol consumption, physical activity participation, physical examination participation, and the fitness expenditure.Results Hypothesis 1: HS significantly promote PB by decreasing the probability of smoking and drinking, increasing the probability of taking exercise and physical examination, and increasing the fitness expenditure. Hypothesis 2 and 3: HSs increase PR, and PR is positively associated with PB. Hypothesis 4: The indirect effects of HS on smoking (−0.016, p<0.05), drinking (−0.015, p<0.001), exercise (0.050, p<0.001), physical examination (0.090, p<0.001), fitness expenditure (0.008, p<0.001) indicate that the relationships between HS and PB are partially mediated by PR.Conclusions This study proves the positive impact of HS on PB was mediated by PR. The findings offer valuable insights for researchers seeking to understand the mechanisms through which HS influences PB and provide healthcare practitioners with an effective approach to leverage teachable moments for delivering targeted preventive services and promoting PB change.